The Influence of Product Quality, Price, and Promotion on Product Purchase Decisions at AW Cosmetics Store - Nur Ainun Br Damanik; Ade Parlaungan Nasution; Fauziah Hanum (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the effect of product quality, price, and promotion on purchasing decisions at Toko AW Kosmetik. The research employs a quantitative approach using a survey method. The population consists of all consumers of Toko AW Kosmetik, with samples selected through an accidental sampling technique. Data was collected through questionnaires that had been tested for validity and reliability. The data analysis techniques include classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results indicate that partially, product quality has a positive and significant effect on purchasing decisions. Price also has a positive and significant effect on purchasing decisions, indicating that the suitability of price with the benefits received is a primary consideration for consumers. Promotion is proven to have a positive and significant effect on purchasing decisions, where the intensity and attractiveness of promotional activities can increase consumer interest and encourage purchasing actions. Simultaneously, product quality, price, and promotion have a significant effect on purchasing decisions at Toko AW Kosmetik. The coefficient of determination shows that the independent variables explain a substantial proportion of the variance in purchasing decisions, while the remaining variance is influenced by other factors outside the research model. In conclusion, improving product quality, setting competitive prices, and implementing effective promotional strategies are key factors in increasing consumer purchasing decisions at Toko AW Kosmetik.